COUMARIN DERIVATIVE CITROPTEN AMELIORATES INFLAMMATION-INDUCED DEPRESSION BY SUPPRESSING PRO-INFLAMMATORY CYTOKINES AND RESTORING ANTIOXIDANT DEFENSE: AN IN VIVO STUDY - PRADEEP KUMAR MOHANTY; VIKRAM P JADHAV (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: Citropten (CP), a naturally occurring coumarin with reported antioxidant and anti-inflammatory effects, has not yet been comprehensively evaluated for antidepressant activity. The present investigation is designed to evaluate the antidepressant-like ability of CP in mice challenged with lipopolysaccharide (LPS) by evaluating behavioral performance, brain neuroinflammatory cytokines, and markers of oxidative stress. Methods: Swiss albino male mice were pre-treated orally for 15 days with vehicle, CP with 25 and 50 mg/kg, or fluoxetine with 20 mg/kg. On day 15, they received a LPS injection intraperitoneally (0.83 mg/kg). Functional behavioral responses were tested on day 16 using the forced swim test (FST), tail suspension test (TST), and open field test (OFT). Furthermore, mice brain tissues were collected to analyze cytokines, such as interleukin (IL)-6, tumor necrosis factor-α, and IL-1β, and stress markers (glutathione [GSH], malondialdehyde [MDA], and catalase [CAT]). Results: LPS treatment led to a significant rise in immobility time in the FST (164.2±9.3 s vs. 115.5±4.5 s; p<0.001) and TST (172.0±7.6 s vs. 120.7±3.9 s; p<0.001) and reduced OFT exploration. CP produced clear dose-dependent improvement with a 50 mg/kg dose, reducing immobility to 91.2±5.8s (FST) and 104.8±7.9s (TST; p<0.001), comparable to fluoxetine. LPS increased brain cytokines by 4–5 fold and caused oxidative imbalance (↑MDA, ↓GSH, ↓CAT), while CP suppressed cytokine levels and restored antioxidant defenses (reduced MDA; increased GSH and CAT). Conclusion: In mice exposed to LPS, CP demonstrated robust antidepressant-like efficacy through simultaneous suppression of central inflammatory responses and mitigation of oxidative stress, indicating promise for treating inflammation-linked depression.